Etos Profesionalisme Kerja Para Nabi dalam Al Quran - Subhan Nur (Jurnal Bimas Islam, 2017)
The Prophets and The Apostle were Allah’s human noble. In addition to do the preaching activities the prophets and apostle did economic activity such as trade, farm, woven, and others. The economic activity aims to become a role model and learn in implementing the 5 values of work ethic professionalism among others: integrity, commitment, innovation, example, and spirituality. Al Qur'an has described the work ethic in stark portraits of The Prophets that we should follow as a guide. The Prophets and Apostles have taught that humans are creatures of bio-psychosocial and spiritual. Because that's the work ethic, being mandatory the presence for the nation success. Nabi dan rasul adalah manusia mulia di sisi Allah SWT. Selain melakukan aktivitas dakwah, para nabi dan rasul melakukan aktivitas ekonomi seperti berniaga, berternak, bertenun, dan lain sebagainya. Aktivitas ekonomi tersebut bertujuan agar menjadi teladan dan pelajaran dalam menerapkan 5 nilai etos profesionalisme kerja antara lain: Integritas, komitmen, inovasi, keteladanan, dan spiritualitas. Al-Qur’an telah menggambarkan secara gamblang potret etos kerja para Nabi yang patut kita tiru sebagai pedoman. Para nabi dan rasul telah mengajarkan bahwa manusia adalah makhluk bio-psikososial dan spiritual. Karena itulah, etos kerja menjadi wajib adanya bagi kesuksesan sebuah bangsa.